2016
DOI: 10.5935/1676-2444.20160058
|View full text |Cite
|
Sign up to set email alerts
|

Polymethyl methacrylate (Linnea Safe) causes local inflammatory response after intramuscular implant in BALB/c mice but it is not observed in distant organs

Abstract: The history of muscle biopsy dates back to 1860, when Duchenne first performed a biopsy on a patient with symptoms of myopathy (1) . Since then, the basic and clinical science of muscle and muscle disease has gone through three stages of development: the classical period, the modern stage and the molecular era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Since its registration, it has been rigorously inspected regarding its quality control. Some Brazilian researchers have studied this product in its first version known as Newplastic ® or in its current one marketed as Linnea Safe ® and have reported that this product leads to a local response with predominance of mononuclear cells infiltration that may turn chronic or not depending on the uniformity of the microspheres. Besides Costa et al showed that this product does not migrate to other organs or locations other the ones where the implant occurred.…”
Section: Case Reportmentioning
confidence: 99%
“…Since its registration, it has been rigorously inspected regarding its quality control. Some Brazilian researchers have studied this product in its first version known as Newplastic ® or in its current one marketed as Linnea Safe ® and have reported that this product leads to a local response with predominance of mononuclear cells infiltration that may turn chronic or not depending on the uniformity of the microspheres. Besides Costa et al showed that this product does not migrate to other organs or locations other the ones where the implant occurred.…”
Section: Case Reportmentioning
confidence: 99%